(3YTQI CjGe gRJ GdYGde (B:s (3hUa TGgO YjGf dKhQI CcJhHQ GdQhSjI YGe (B1917 /s - (3QjO, Lhfs 1887-1920; (3QjO, Lhf,s 1887-1920.; (3WQGHdSj, ahGR,s 1941- ((3ejdGfh, EjWGdjG (B:s (3efThQGJ GdeJhSW,s, 2019)
(3jSJQLY gPG GdcJGH HcKGaI hMOI eOgTJjf GdCjGe GdChdi ef KhQI CcJhHQ(B. (3EffG dG fdbi gfG eLQO JYOGO ddCMOGK, Ch eLehYI ef GdhKGFb, hEfeG SdSdI ef GdeTGgO GdeYGTI, UGObI Edi OQLI CfgG dG HO hCf JSJQLY aj Pgf cd GdPjf YGjThG GdKhQI GdeTGgO GdJj MVQhgG(B. (3Ef cd gPg GddhMGJ, GdeQSheI HObI, JYHQ Yf eTGYQ GdLeGgjQ(B. (3hJSeM HGdJGdj Hage GdeYfi GdMbjbj deNJda CWhGQ GdKhQI GdYXjeI(B. (3bO jHOh ZQjHG, dChd hgdI, Cf jchf eDda gPG GdcJGH CLfHjG, CeQjcjG jLgd dZI GdHdO hJbGdjOg(B. (3jHOh hcCf dG HO dg ef Cf jQJcH CLSe GdCNWGA, YfO cd NWhI, hCf jJZGad Yf YhGed CSGSjI(B. (3Ef GdcqJGH GdCLGfH dG jcJHhf Yf QhSjG GdShajjJjI ceG jcJH Lhf QjO, aEeG Cfge dG jagehf eYfi GdCMOGK, hEeG Cf jdLChG Edi GdJYeje GfWdGbG ef hbGFY eYRhdI dG Jchf gj GdhbGFY GdCSGSjI GdeejRI(B. (3hUMjM Cf Gdbdjd efge abW bO TGgO GdKhQI TNUjG(B.s
Keywords: (3GdTjhYjIs -- (3GdGJMGO GdShajJjs; (3QhSjGs -- (3GdGMhGd GdSjGSjIs -- (3GdYUQ GdMOjKs